Isolation and Identification of Bacteria from Phytoremediation Plant of Heliconia psittacorum. Issue 1 (August 2020) - Baharuddin, Mior Izzuddin; Kamarul Baharin, Syahirah Naailah; Rak, Aweng Eh; Hanaphi, Roziana
Abstract: Phytoremediation is a technology that uses plants to degrade, assimilate, metabolize, or decompose organic matter and pollutants. Critical criteria for plants used for phytoremediation include economic benefits, harvest management, and side-use. This cost-effective plant-based recovery utilizes exceptional plant and microorganism capabilities to focus on environmental elements and compounds and metabolize various molecules in their tissues to decompose elements such as heavy metals, toxic substances, and organic pollutants are the main targets. This study aims to analyze the concentration of Gram-positive and Gram-negative bacteria and identify the bacteria using biochemical assays and commercialized API Kit (Biomerieux, France). Three plant samples of Heliconia psittacorum were analyzed for their root and soil sample which showed the concentration of Gram-positive bacteria is higher compared to Gram-negative bacteria which ranged from 1.9 x 108 to 3.95 x 109, while gram-negative bacteria ranged from 2.25 x 107 to 2.95 x 109. Based on the identification test, seven bacteria were identified. Four gram-negative bacteria are Enterobacter aerogenes, Escherichia coli, Pseudomonas aeruginosa and Chryseobacterium indologenes which are generally bacteria that are common to the environment. Meanwhile, three gram-positive bacteria include Staphylococcus aureus, Staphylococcus xylosus, and Staphylococcus lentus have a high impact on metal degradation in the effluent. In conclusion, the concentration of bacteria is relatively higher in the root area of the plant which dominated by gram-positive bacteria and the bacteria that were identified have a prominent effect on the phytoremediation process.